Expanding The Benefits of Waqf For The Environment In Waqf Policy In Indonesia - Sulistiani, Siska Lis; Maryandi, Yandi; Hayatudin, Amrullah (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2026)
Waqf in Indonesia has been known since before Indonesia's independence with a narrow waqf nomenclature and limited to the purpose of religious facilities and education only. Waqf assets are widely known to be only in the form of land and buildings which are limited in their use and management so that they seem unattractive. In accordance with the results of the waqf literacy index of the Indonesian Waqf Agency (BWI) regarding the level of public understanding regarding waqf which is still minimal. Meanwhile, natural problems in Indonesia are increasing and require mitigation efforts from various aspects, one of which is waqf. The purpose of this study is to analyze the opportunities for expanding the benefits of waqf to protect the environment and minimize the impact of ecological disasters in Indonesia, through applicable regulations and policies. The research method used is a literature study through legal and policy study materials relevant to waqf. The results of this study indicate that the benefits of waqf can be expanded according to conditions and times without reducing the main standards that have been conveyed by the Prophet Muhammad in the hadith of Umar. In addition, the Waqf Law No. 41 of 2004 still needs to be changed, especially regarding the scheme for regulating and providing policies for the benefits of waqf for the environment, which can be collaborated with other financial sectors in accordance with sharia and legal provisions in Indonesia so that it can become one of the solutions to social problems in society. [Wakaf di Indonesia sudah dikenal sejak sebelum Indonesia Merdeka dengan nomenklatur wakaf yang sempit dan terbatas pada tujuan sarana agama dan Pendidikan saja. Asset wakaf banyak diketahui hanya berbentuk tanah dan bangunan yang secara penggunaan dan pengelolaannya yang terbatas sehingga terkesan tidak menarik. Sesuai dengan hasil indeks literasi wakaf Badan Wakaf Indonesia (BWI) terkait Tingkat pemahaman Masyarakat terkait wakaf yang masih minim. Sedangkan permasalahan alam di Indonesia semakin banyak dan memerlukan Upaya mitigasi dari berbagai macam aspek, salah satunya wakaf. Tujuan penelitian ini adalah menganalisis peluang perluasan manfaat wakaf untuk menjaga lingkungan dan meminimalisir dampak bencana ekologi di Indonesia, melalui regulasi dan kebijakan yang berlaku. Metode penelitian yang digunakan adalah studi pustaka melalui bahan kajian hukum dan kebijakan yang relevan dengan wakaf. Hasil penelitian ini menunjukkan bahwa manfaat wakaf dapat diperluas sesuai dengan kondisi dan zaman tanpa mengurangi standar utama yang telah disampaikan oleh Nabi Muhammad dalam hadis Umar. Selain itu, Undang-Undang Wakaf No. 41 Tahun 2004 masih perlu dilakukan perubahan terutama mengenai skema pengaturan dan kebijakan manfaat wakaf bagi lingkungan yang dapat dikolaborasikan dengan sektor keuangan lain yang sesuai dengan ketentuan syariah dan hukum di Indonesia sehingga dapat menjadi salah satu Solusi permasalahan social kemasyarakatan.]